Special education public policies and FENAPAE's under the gramscian perspective - Douglas Christian Ferrari de Melo; João Henrique da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The work aims to reflect on contradictory relations between public Special Education policies and FENAPAES's position on scholar inclusion. One carried out the documental analysis of Special Education normative texts along with the federation text that takes stand for the permanence of special schools. Data were analyzed under Gramsci's view. Results evidenced that APAEs corresponds to a civil society that acts within the State, by means of which they occupy their space in the political hegemony over education for impaired people. Public policies, subject to production demands and social conditions of a given historical moment, are planned in accordance with the federation and articulated with the project of an inclusive school. The clash regarding inclusive education within the State reveals that its goals are neoliberal as it searches for the support of its systems in order to maintain the hegemony over which education must be granted.